História, Literatura e Memória: reflexões sobre a Grande Guerra (1914-1918) - Martins, Luciana de Lima (2008)
This dissertation thesis reflects upon the Great War (1914 1918), from the Historiography, analyzing the romances All Quiet on the Western Front, written by Erich Maria Remarque and A Farewell to Arms, written by Ernest Hemingway, and, consequently, their constructed memories. Both the Historical and the Literary knowledge relates to group and individual experiences from the present and the past. Since they reflect upon the past, they contribute to the construction of historical cultures. The extension, the length and the brutality of the First World War, characterized as a paradigmatic moment in the 20th century, has contributed for the construction of historical cultures that, aside their ifferences, question and search for a comprehension of the historical moment.